Analisis Metode SMARTER Dalam Sistem Pendukung Keputusan Penerima Bantuan Raskin - Julfikar Julfikar; Volvo Sihombing (Jurnal Sistem Informasi, Teknik Informatika dan Teknologi Pendidikan, 2021)
The problem of poverty is a classic problem that occurs in every country, both developed countries and developing countries like Indonesia. in every country there are many programs carried out by the government to overcome the problem of poverty, one of which is the RASKIN program carried out by the Indonesian government. The method used to complete this research is SMARTER (Simple Multi Attribute Rating Technique Exploiting Ranks). The SMARTER method was chosen because it is a form of decision support model used in decision making with multiple attributes that will be used to solve decision-making problems. The research was conducted in Sei Beluru Village, Meranti District, Asahan Regency. In Sei Beluru Village, the criteria are the floor area of ​​the house, type of house floor, type of house walls, toilet facilities, drinking water sources, lighting, fuel used, frequency of eating, ability to buy meat, ability to buy clothes, ability to seek treatment, income. per month, education of the head of the household, asset ownership. The decision support system using the smarter method is able to analyze data on people who are entitled to receive Raskin assistance.